(untitled) (World Bulletin of Management and Law, 2022)
Today, special attention is being paid to structural restructuring of our country’s economy, improvement of the structure of the gross domestic product by increasing the production of industrial products, creation of the added value chain. This article analyzes the world experience of structural policy improvement and its use in the economy of our country